DINAMIKA PSIKOLOGIS SENIMAN PEREMPUAN DALAM PROSES PENCIPTAAN KARYA SENI LUKIS - , Lia Mareza, Dr. Wisjnu Martani, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2013)
There are three research questions posed in the study, i. e. (1) background what motives women to become artists and how they motivate themselves in a work of art for sake of its existence? (2) how artists interpret the messages contained in the process of creating a work art? And (3) how does the psychological dynamics of women artists in the procedd of creating a work of art?. The third question this research is a unity of ideas in order to reveal the psychological dynamics of women artists in the process of creating works of art painting. In order to reveal the answer to the three questions, the data collected techniques through of observation, interview and librarianship, and used a qualitative approach based on the phenomenological theory of the creative process, motivation and emotion of the situation. This research was done in the city of Yogyakarta, with three of the respondents women artists. The selection of respondents in this research was already married, flying hours artists in exhibition, and still works to this day. The results of this research to find out four research findings, i.e. (1) painter let emotions distort the objects he saw